MINI REVIEW : SINTESIS KOMPOSIT Fe3O4/ARANG AKTIF SEBAGAI MEDIA ADSORPSI - Laurentha, Nantha; Hindryawati, Noor (PROSIDING SEMINAR KIMIA, 2025)
Mini review of Fe3O4/activated carbon composite synthesis as adsorption media. The purpose of this mini review is to optimize adsorption efficiency through variations of different types of activated carbon. The Fe3O4/activated carbon composite is used as adsorption media due to its high adsorption capacity, and the magnetic properties of Fe3O4 facilitate the separation of the composite from the solution after the adsorption process. Based on a literature review, the Fe3O4/activated carbon composite can be synthesized using the co-precipitation method, and characterization is performed using Fourier Transform Infrared Spectroscopy (FTIR), and X-Ray Diffraction (XRD). Therefore, this article reviews recent developments regarding the Fe3O4/activated carbon composite as an adsorption medium for dye wastewater. Keywords : Fe3O4, activated carbon, composite, adsorption.